KETERLIBATAN LAKI-LAKI DALAM KESETARAAN GENDER - Moh. Faiz Maulana (Jurnal Anifa: Studi Gender dan Anak, 2022)
The movements carried out by women for gender justice and the elimination of violence against women in Indonesia have not only changed women's perspective on efforts to fight women against the violence that occurred to them but have also inspired some men and produced new perspectives. Seeing themselves and growing new awareness about their need to be actively involved in the movement against violence against women. This study uses a qualitative method with a literacy study approach regarding men's involvement in gender equality efforts, using the theory of hegemonic masculinity. Hegemonic masculinity is used to criticize the male sex role. Sources of data used are secondary data, such as scientific articles, reference books, journal publications, websites, and other sources relevant to the topic of study. Furthermore, data were collected, grouped, analyzed, and interpreted using the perspective of gender and feminism to describe results and research discussions. This paper tries to explain that gender inequality or even violence against women is difficult to fight if there is no collaboration from various parties, one of which is men; men are at the root of the problem of violence against women, so they must also be part of solving the problem.